Immunological signature of patients with thymic epithelial tumors and Good syndrome - Malfitano, Anna Maria; D’Esposito, Vittoria; De Placido, Pietro; Tortora, Marianna; Ottaviano, Margaret; Pietroluongo, Erica; Morra, Rocco; Mucci, Brigitta; Napolitano, Fabiana; Montella, Liliana; Giuliano, Mario; De Placido, Sabino; et al. (Frontiers in Immunology, 2022)
Background Thymic epithelial tumors (TETs) are frequently accompanied by Good Syndrome (GS), a rare immunodeficiency, characterized by hypogammaglobulinemia and peripheral B cell lymphopenia. TETs can be also associated to other immunological disorders, both immunodeficiency and autoimmunity. Methods In this study, we enrolled TET patients with GS to address differences between patients with or without associated autoimmune diseases (AD). We analyzed the immunophenotype from peripheral blood of these patients focusing on selected immune cell subsets (CD4+T cells, CD8+T cells, T regulatory cells, NK cells, B-cells, monocytes, eosinophils, basophils, neutrophils) and serum levels of cytokines, chemokines and growth factors. Results We observed higher number of leucocytes, in particular lymphocytes, B lymphopenia and lower number of T regulatory cells in TET patients with associated AD compared to TET patients without AD. In the group of TET patients with AD, we also observed increased serum levels of IL-15, VEGF, IP-10, GM-CSF, IL-6, and MIP-1α. Thus, we identified considerable differences in the lymphocyte profiles of TET patients with and without ADs, in particular a reduction in the numbers of B lymphocytes and T-regulatory cells in the former, as well as differences in the serum levels of various immune modulators. Conclusions Although the pathogenic mechanisms are still unclear, our results add new knowledge to better understand the disease, suggesting the need of surveilling the immunophenotype of TET patients to ameliorate their clinical management.